Decolorization of Synthetic Dyes by Tropical Fungi Isolated from Taman Eden 100, Toba Samosir, North Sumatra, Indonesia - Sita Heris Anita; Fenny Clara Ardiati; Kharisma Panji Ramadhan; Raden Permana Budi Laksana; Fahriya Puspita Sari; Oktan Dwi Nurhayat; Dede Heri Yuli Yanto (HAYATI Journal of Biosciences, 2022)
Taman Eden 100 is one of the tourist parks located in Toba Samosir, North Sumatra, Indonesia that provides a wide range of biodiversity. The objective of this research was to obtain the potential fungal isolate with high laccase activity to decolorize synthetic dyes. The results show that six isolates of Perenniporia subtephropora EDN 050, Trametes hirsuta EDN 082, T. hirsuta EDN 084, T. hirsuta EDN 085, Deconica coprophila EDN 114, and T. pavonia EDN 134, which were confirmed by molecular identification using 5.8 rDNA/ITS analysis, exhibited decolorization activity. Six potential isolates showed the ability to decolorize textile dyes of Acid Blue 129, RBBR,Orange II, and Reactive Black 5. The highest decolorization rate of 100 ppm Acid Blue 129, RBBR, Orange II, and Reactive Black 5 dyes by using T. pavonia EDN 134 were 98.87%, 98.26%, 100%, and 98.11%, respectively after 96 h incubation. Almost all positive isolates also decolorized dyes at higher concentrations (1,000 ppm). This study offers the potential of Indonesian tropical fungal isolates for synthetic dyes waste treatment.